1971
DOI: 10.1038/icb.1971.69
|View full text |Cite
|
Sign up to set email alerts
|

RELATIVE EFFICIENCY OF ABSORPTION OF IgG1 IgG2, IgA AND IgM IN THE NEWBORN CALF

Abstract: Summary. To detenniiie whether selective absorption of immunoglobulin occurs in newborn unamiesthetised calves, the concentrations of IgGj, IgG^. IgM and IgA were measured in thoracic duct lymph shortly after the feeding (if colo.strum. In the 13 calvx-s studied it was found that the coiicenlrations of IgC|, IgCj, IgM and IgA in lymph expressed as a proixtrtiun of the concentration of the same immunoglobulins in the colostrimi fed were not siffnificantly different. It i.s concluded that immunoglobiiluis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…The half-life of the two major IgG isotypes (IgG1, IgG2) have been reported in several studies but the values are extremely divergent between publications (for a review, see Butler (56)). However, the data indicate that they both fall in the range of 10 -22 days (60,61), with a longer half-life for IgG2 (62,63). Based on the positive correlation between binding affinity and halflife, these data may suggest that IgG2 binds more effectively to the FcRn than IgG1.…”
Section: Bovine Igg Metabolismmentioning
confidence: 77%
“…The half-life of the two major IgG isotypes (IgG1, IgG2) have been reported in several studies but the values are extremely divergent between publications (for a review, see Butler (56)). However, the data indicate that they both fall in the range of 10 -22 days (60,61), with a longer half-life for IgG2 (62,63). Based on the positive correlation between binding affinity and halflife, these data may suggest that IgG2 binds more effectively to the FcRn than IgG1.…”
Section: Bovine Igg Metabolismmentioning
confidence: 77%
“…A redução na concentração sérica de imunoglobulinas durante o período pré-parto, observada em bovinos, está associada à remoção ativa desses anticorpos pela glândula mamária (Larson & Kendall, 1957;Sasaki et al, 1976). Em bovinos nas três últimas semanas pré-parto, pesquisadores têm observado mobilização de 500 a 700 g de imunoglobulinas do sangue para a glândula mamária (Dixon et al, 1961;Brandon & Lascelles, 1971;Foley & Otterby, 1978).…”
Section: Resultsunclassified
“…This transport system explains the very different ratio between IgGl/ IgG2 in colostrum and plasma. Fixation sites with a very high affinity (Sasaki et al, 1977) for IgG have been clearly identified on the basal membranes of glandular epithelium cells (Brandon and Lascelles, 1971;Hammer and Mossman, 1978). These cells proliferate during the period of mammary growth preceding parturition and their growth is affected by oestradiol 17-beta (Delouis, 1978).…”
Section: Origin Of Colostral Antibodiesmentioning
confidence: 99%
“…In ungulates, the IgG are predominantly IgGl. In the cow, 85% of total colostrum Ig are IgG with 95% IgGl and only 5% IgG2 (review by Berthon and Salmon, 1993) whereas, in the blood the IgG are much more balanced, 55 and 45%, respectively (Brandon and Lascelles, 1971;Beer et al, 1974). In pig colostrum as opposed to cow's, IgG are only twice as abundant as IgA (Jensen and Pedersen, 1979).…”
Section: Type Of Colostral Antibodiesmentioning
confidence: 99%